Catalytic ozonation of 2-hydroxy-1,2,3-propanetricarboxylic acid - Ngadi, Norzita; Saidina Amin, Nor Aishah; Khew, Shih Tak; Lai, Siok Lian; Lau, Kok Keong (Penerbit UTM Press, 2006)
Catalytic ozonation is an Advanced Oxidation Processes (AOP) where the ozone is applied together with catalyst in homogeneous or heterogeneous form. The heterogeneous catalytic ozonation of 2-hydroxy-1,2,3-propanetricarboxylic acid using powdered HZSM-5, Cu-ZSM-5, Mn-ZSM-5 and V-ZSM-5 with different mole ratio of SiO2/Al2O3 as catalyst were studied. The effectiveness of catalytic ozonation compared with non-catalytic ozonation, the effect of loaded metal onto ZSM-5 and the performance of each catalyst are tested in this work. The effect of ozone gas bubble size is also investigated. The experiment had been carried out in an agitated semibatch reactor under some fixed experimental parameters. Acid-base titration was used to analyze the collected product. The results show that the presence of catalyst has improved the ozonation rate of 2-hydroxy-1,2,3-propanetricarboxylic acid by 25% as compared to the results of non-catalytic ozonation. Different catalysts with different mole ratio of SiO2/Al2O3 have different performance in this catalytic ozonation. However, most of the catalysts show the highest conversion rate at SiO2/ Al2O3 mole ratio of 80. In overall, V-ZSM-5 catalyst could promote the ozonation process better than Cu-ZSM-5 and Mn-ZSM-5. The results also show that ozone gas with smaller bubble size gave better performance